Enhancing Surgical Accuracy: Integrating Robotics, AI, and Deep Learning in Dentistry and Microbiology - N K Achar, Shashank; Bhushan Mall, Braj; Kumar Sahu, Deepak; Batra, Poonam; Bandyopadhyay, Sukanta (Journal of Neonatal Surgery, 2025)
The incorporation of innovative technologies, such as robotics, artificial intelligence (AI), and deep learning, has transformed the medical sector, especially in surgery. Dentistry and microbiology, two healthcare fields of great importance, have much to benefit from these new technologies. Surgery is made more precise and dexterous through robotics, and AI offers real-time decision support, which facilitates treatment planning and diagnostics. Deep learning, by virtue of its capacity to learn from massive datasets, greatly enhances procedural and diagnostic precision. This paper considers the application of robotics, artificial intelligence, and deep learning in enhancing surgical precision in dentistry and microbiology in the context of recent developments, practical uses, and the challenges of their integration. The article also delves into the capacity of these technologies to revolutionize dental and microbiological procedures through enhanced clinical performance, minimizing mistakes, and maximizing patient treatment. As they progress, the technologies have the promise of increasing the levels of surgical practice to an even higher degree, increasing the efficiency, accuracy, and availability of procedures. Challenges, including prohibitive expenses, necessity for training in specialization, and issues of regulatory oversight, remain a hindrance to extensive utilization. This report highlights the revolutionary potential of these technologies while recognizing the challenges that must be overcome to successfully implement them in healthcare environments